Hydrothermal silicification confined to stratigraphic layers: Implications for carbonate reservoirs. (February 2021) - Souza, Victor H.P.; Bezerra, Francisco H.R.; Vieira, Lucieth C.; Cazarin, Caroline L.; Brod, José A.
Abstract: Hydrothermal silicification generates secondary porosity and permeability and could play an important role in carbonate reservoirs. We investigated the Cristal Cave, which is hosted in carbonate units of the Caboclo Formation, São Francisco Craton, Brazil, to assess the role of sedimentary facies and stratigraphy in hydrothermal silicification. Our results indicate that in the cave area, the carbonate units are composed of (1) ooidal grainstones, (2) intraclastic grainstones and rudstones, (3) heterolites, (4) marls, (5) stromatolites, (6) oncolithic-intraclastic grainstones and rudstones, and (7) hydraulic breccias. QEMSCAN and energy dispersive X-ray spectroscopy (EDS) analyses show that hydrothermal silicification is the most common diagenetic process in these rocks and reveal a mineral paragenesis composed of quartz, chalcedony, K-feldspar, barite, hyalophane (Ba-feldspar), talc, and chlorite. The marls (Unit 4) are impermeable rocks that represent a maximum flooding surface and divide the sedimentary succession into a bottom and an upper interval. They behaved as a sealing unit that prevented the upward flow of silica, channeling hydrothermal silicification in the bottom stratigraphic interval. Within the silicified interval, units 1, 2, and 3 show great differences in the degree of silicification since the ooidal grainstones (Unit 1) concentrated the hydrothermal fluids, reaching the highest degree of silicification in the stratigraphic column. We conclude that the stratigraphic framework can control the vertical distribution of hydrothermal fluids and the development of layer-parallel fluid flow conduits. The Cristal cave serves as an analog, which could contribute to the understanding of silicified carbonate reservoirs. Highlights: We study hydrothermal silicification (HS) in karstified carbonate units. The mineral paragenesis in carbonate units indicates hydrothermal fluids. HS was concentrated in ooidal grainstones below a siliciclastic seal. Lithology controlled hydrothermal fluid flow and subsequent karstification.